Vivências e significados dos transtornos alimentares através da narrativa de mulheres - Souto, Silvana Gonçalves (2002)
This research investigates, through the narrative of women, the experience and the meaning of Eating Disorders (ED) considering the intra-personal, familiar and socialcultural dimensions. These women are currently being under an inter-disciplinary follov^."- up at the Center of Studies and Treatments in Eating Disorders (CETRATA) of the Federal University of Ceará or in a private clinics, in the city of Fortaleza- Ceará, Northeast of Brazil. A qualitative approach was used for data collection by individually inten'iewmg seven women, aged 13 to 52 years. Three of them suffering from Anorexia Nen'osa. t\\~o Bulimia Nervosa and two, Binge Eating Disorder. Through data analysis Ae units of sigmfication were identified first and the'sense nucleus related to the generator theme. After that, by using the association of ideas mapping techniques categories of analysis were defined. They constituted the main themes of the study. Diagrams of meaning v.'ere constnicted to analysis. The study highlights similarities and divergences in the three types of Eating Disorders, such as: personal and/or family history of overweight/obesity, desire of being thin, morbid fear to get fat, wrong diet practices, use of inadequate mechanisms of weight control, suffering of child abuses (physical, emotional, sexual), presence of family's secrets, personal, family's and/or socio-cultural incentives to dieting and to look slim. The study also shows the inadequacy of the biomedical model and it points out that patients suffering ED'S need to be assisted by a well qualified interdisciplinar)' team. specialized and cohesive. The development of attendance strategies, where the nutritional approach occurs through the alimentary re-education is suggested.